'As syllable from sound': the sonic dimensions of confinement at the State Hospital for the Insane at Worcester, Massachusetts. Issue 1 (March 2020) - Bourque Kearin, Madeline
As the first state hospital in the USA, the Worcester State Hospital for the Insane at Worcester, Massachusetts (est. 1833), set a precedent for asylum design and administration that would be replicated across the country. Because the senses were believed to provide a direct conduit into a person's mental state, the intended therapeutic force of the Worcester State Hospital resided in its particular command over sensory experience. In this paper, I examine how aurality was used as an instrument in the moral architecture of the asylum; how the sonic design of the asylum collided with the day-to-day logistics of institutional management; and the way that patients experienced and engaged with the resultant patterns of sound and silence.